Implikasi Yuridis Putusan Mahkamah Konstitusi Nomor 28/Puu-Xxiii/2025 terhadap Pengaturan Royalti dan Tanggung Jawab Hukum dalam Penggunaan Lagu Secara Komersial - Diyara Eninta Br Sitepu; Suhaidi; Jelly Leviza (Jurnal Hukum Lex Generalis, 2026)
Copyright as part of Intellectual Property Rights plays an important role in protecting musical works and ensuring the moral and economic rights of creators. However, the implementation of Law Number 28 of 2014 still gives rise to multiple interpretations, particularly regarding the party responsible for paying royalties and the meaning of reasonable remuneration, which has led to conflicts. This normative juridical research applies a statutory approach and the theory of legal certainty. The results show that Constitutional Court Decision Number 28/PUU-XXIII/2025 affirms event organizers as the parties obligated to pay royalties, establishes standards for remuneration, strengthens the role of Collective Management Organizations and positions criminal sanctions as an ultimum remedium to enhance legal certainty and protect creators, while encouraging regulatory harmonization and transparency in the national music industry.